FEASIBILITY OF CONTINUOUS ACTIGRAPHY IN PATIENTS IN A MEDICAL INTENSIVE CARE UNIT. - Kamdar, Biren B.; Kadden, Daniel J.; Vangala, Sitaram; Elashoff, David A.; Ong, Michael K.; Martin, Jennifer L.; Needham, Dale M. (American Journal of Critical Care, 2017)
Background Poor sleep and immobility are common in patients in the medical intensive care unit (MICU) and are associated with adverse outcomes. Interventions to promote sleep and mobilization in the MICU are gaining popularity, but feasible instruments to measure their effectiveness are lacking. Actigraphy may be useful for large-scale, continuous measurement of sleep and activity, but its feasibility in MICU patients has not been rigorously evaluated. Objective To evaluate the feasibility of continuous actigraphy measurement in consecutive MICU patients. Methods Wrist and ankle actigraphy data were collected for 48 hours in consenting MICU patients. Actigraphybased measures of estimated sleep and activity were summarized by using descriptive statistics. Agreement between wrist and ankle measurements was evaluated using Cohen κ statistics (for sleep quantity) and intraclass correlation coefficients (for activity). Results Overall, 35 of 48 (73%) eligible patients were enrolled, including 10 requiring mechanical ventilation. Of these patients, 34 (97%) completed the 48-hour actigraphy period; 20 (57%) found the devices comfortable. Wrist devices logged a mean (SD) of 33.4 (8.8) hours of estimated sleep (72% [19%] of recording period) and 19.6 (17.2) movements per 30-second epoch. Ankle devices recorded 43.2 (4.1) hours of estimated sleep (93% [7%] of recording period) and 5.1 (6.0) movements per 30 seconds. Conclusions Uninterrupted actigraphy is feasible and generally well tolerated by MICU patients and may be considered for future large-scale studies. Wrist and ankle actigraphy measurements of sleep and activity in this setting agree poorly and cannot be used interchangeably.